NUMERICAL INVESTIGATION OF GEOPOLYMER REINFORCED CONCRETE BEAMS UNDER FLEXURAL LOADING USING 3DNLFEA - Yosi Noviari Wibowo; Bambang Piscesa; Yuyun Tajunnisa (Journal of Civil Engineering, 2022)
This paper deals with numerical modeling of geopolymer reinforced concrete loaded under flexure using nonlinear finite element analysis. The modeled specimen was obtained from the existing literature and is tested under the four-point bending load. The numerical simulation uses an in-house limited element package called 3D-NLFEA, which utilizes ordinary concrete's multi-surface plasticity model. Since the concrete constitutive model used is for ordinary Portland cement, adjusting the input parameter is required to predict the behavior of geopolymer reinforced concrete. The focus on the discussion was limited to the modeling of the specimen, the moment-curvature result, and the crack pattern between the numerical model and the available experimental test. The simulation found that the predicted moment-curvature relationship using the 3D-NLFEA package was 1.3 to 2.4 % lower than the test result. The crack pattern was controlled by flexure, which was observed in the experimental test and numerical simulation. The predicted crack lengths for modeled beam using 3D-NLFEA were within the minimum and maximum measured crack lengths from the test result.